2022
DOI: 10.3390/biology11030350
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Mesenchymal Stromal Cells Delivered during Hypothermic Oxygenated Machine Perfusion Repair Ischemic/Reperfusion Damage of Kidneys from Extended Criteria Donors

Abstract: The poor availability of kidney for transplantation has led to a search for new strategies to increase the donor pool. The main option is the use of organs from extended criteria donors. We evaluated the effects of hypothermic oxygenated perfusion (HOPE) with and without extracellular vesicles (EV) derived from mesenchymal stromal cells on ischemic/reperfusion injury of marginal kidneys unsuitable for transplantation. For normothermic reperfusion (NR), we used artificial blood as a substitute for red blood cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 102 publications
(115 reference statements)
1
17
0
1
Order By: Relevance
“…Similar positive results were obtained in a single-centre, prospective, pilot, randomized clinical study that evaluated the effects of 4 h of hypothermic oxygenated machine perfusion with and without the delivery of BM-MSC extracellular vesicles on marginal kidney pairs that were considered unsuitable for transplantation 121 . The BM-MSC extracellular vesicle-treated kidneys ( n = 5) showed improved preservation of the renal architecture and mitochondrial morphology, less tubular damage and lower caspase 3 expression (indicating a protective effect against apoptosis) compared with the control perfused kidneys.…”
Section: Therapeutic Use Of Extracellular Vesiclessupporting
confidence: 71%
See 1 more Smart Citation
“…Similar positive results were obtained in a single-centre, prospective, pilot, randomized clinical study that evaluated the effects of 4 h of hypothermic oxygenated machine perfusion with and without the delivery of BM-MSC extracellular vesicles on marginal kidney pairs that were considered unsuitable for transplantation 121 . The BM-MSC extracellular vesicle-treated kidneys ( n = 5) showed improved preservation of the renal architecture and mitochondrial morphology, less tubular damage and lower caspase 3 expression (indicating a protective effect against apoptosis) compared with the control perfused kidneys.…”
Section: Therapeutic Use Of Extracellular Vesiclessupporting
confidence: 71%
“… The addition of stem cell-derived extracellular vesicles to the perfusion solution during machine perfusion of donor kidneys before transplantation might protect the kidney graft from ischaemic damage, stimulate pathways involved in energy metabolism and protect mitochondria and tubular cells from damage and apoptosis 121 . …”
Section: Therapeutic Use Of Extracellular Vesiclesmentioning
confidence: 99%
“…Moreover, the evaluation of lactate, glucose, and LDH in the effluent fluid indicated extensive use of energy substrate in the presence of MSC and MSC EVs. More recently, the same group showed that EVs delivered during hypothermic oxygenated perfusion into marginal kidneys significantly reduces ischemia-reperfusion injury ( Rampino et al, 2022 ).…”
Section: Kidneymentioning
confidence: 99%
“…Recently, the use of “empty” liposomes (no drug loaded) in dialysate during renal dialysis has been investigated, as scavengers both for exogenous intoxicants (intoxicants) and endogenous toxic molecules (endogenous toxins), which accumulate due to decreased excretion in cases of organ failure. Studies showed that intravascular “empty” liposomes, in vivo, act as detoxification vehicles [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scarce literature is reported on transplantation after ex vivo drug administration targeting the biological pathway associated to kidney failure (i.e., oxidative stress, complement system and fibrosis). Recently, extracellular vesicles (EV) from mesenchymal stem cells have been proposed as carriers of a pool of biologic factors that can improve renal survival during ex vivo perfusion [ 13 , 16 , 17 ]. Since liposomes have been demonstrated to be effective drug carriers for kidney targeting, in this preliminary work, we want to explore the ability of formulating liposomes that would be stable in non-physiologic conditions (namely hypothermic conditions and perfusion fluid) for safe and effective delivery to endothelial tubular cells.…”
Section: Introductionmentioning
confidence: 99%